TINJAUAN YURIDIS LEGAL STANDING TERHADAP LEMBAGA PERLINDUNGAN KONSUMEN SWADYA MASYARAKAT (Studi Kasus Nomor Perkara 0931/Pdt.G/2015/Pa.Jmb) - Helfi Adilah; Hayatul Ismi; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The Consumer Protection Agency of Swadya Society is an institution thatwas established to help Indonesian consumers in struggle for the rights ofconsumers who have been harmed by the businesses offender, with litigate to thecourt when deliberations between the two sides cannot be solved properly. In ActNo. 8 of 1999 about consumer protection, describes Consumer Protection Agencyof Swadya Society have legal standing in filing a lawsuit, but in practice judgehave consideration to the Consumer Protection Agency of Swadya Society has nolegal standing in filing a lawsuit to the court. It’s certainly make some questionabout legal standing of Consumer Protection Agency of Swadya Society. Thepurpose of this thesis about : first, to analysis legal standing of ConsumerProtection Agency of Swadya Society. Second, to analysis the judgement about thelegal standing of Consumer Protection Agency of Swadya Society.The type of this research can be classified in types of juridical normativeresearch, because in this research the authors use the study material libraries likeofficial documents, books for research, in this study, the data source using theprimary data, secondary data and tertier data, data collection technique on thisresearch is study of librarianship method or documentary studies.The results of this research can be concluded first, based on act No. 8 of1999 about consumer protection, Consumer Protection Agency of Swadya Societycan filing a lawsuit to the Court because the act explained Consumer ProtectionAgency of Swadya Society can filing a lawsuit to the Court for the benefit ofconsumers and the notion of consumers has been regulated in section 1paragraph (2) of act No. 8 of 1999 about Consumer Protection. Second, thejudgements adjudication Number 0931/PDT. G/2015/PA.Jmb has not fulfilledlegal certainty because inaccurate of the judges in deciding the case andinattention on the regulation about Consumer Protection Agency of SwadyaSociety.Author's suggestion, first, expected judges who adjudicate the case ofconsumer protection must pay attention to the applicable regulation especiallyabout legal standing of Consumer Protection Agency of Swadya Society.Secondly, needed regulation about the lawsuit mechanism of legal standing tocreate legal certainty.Keyword : Legal Standing - Consumer Protection Agency of Swadya Society